Immediate Implant Placement in Mandibular Esthetic Zone: A Clinical Report - M. Krishna1 , Priyanka Basu2 , Abhijita Mohapatra3 , Gopal Krishna Choudhury4 , Krishna Nanda1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
In the past two decades’ immediate dental implant placement has been considered satisfactory treatmentmodality. The dental implants can be placed in the fresh extraction sites by simultaneous use of bone graftmaterial. The patient was suggested to go for a treatment procedure for the extraction of and immediateimplant therapy. A bonegraft material was used to fill the space between the implant and the sockets alongwith planning a two-stage surgical procedure to optimize bone healing. When the osseointegration wascomplete abutment connection was placed with no complications radiographically examination showeda slight marginal bone reduction after 6months of follow-up. The immediate placement of implants helpsin preserving the form and contours of the hard and soft tissues, by decreasing the necessity augmentationprocedure. It also helps in minimizing the surgical exposure of the patient, reducing the treatment time andalso improves the esthetic outcomes.